2022
DOI: 10.3389/fphys.2022.879216
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of the Firefly Pyrocoelia analis (Coleoptera: Lampyridae) to an Environmental Residue From Chemical Pesticide Imidacloprid

Abstract: Imidacloprid, a neonicotinoid insecticide, is widely applied to control insect pests across a broad spectrum. Though the impact of residues from this chemical pesticide on non-target organisms in the field has been reported, it was not well characterized across a wide range of ecosystems, especially for some species considered as environmental indicators that live in forests. The effects of sublethal dose of imidacloprid on firefly, Pyrocoelia analis, were analyzed physiologically and biochemically in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 107 publications
(129 reference statements)
0
4
0
Order By: Relevance
“…Utilizing abundant species (or groups of species) with constricted elevation ranges as bioindicators can help to monitor the effects of climate change on the biota and determine how species are adapting through time. According to their findings, imidacloprid residues may be extremely hazardous to non-target insects in the environment, even in areas far from the agro ecosystem where the herbicides were used (Wang et al, 2022). Their findings showed that the Scarabaeinae fauna of Itatiaia is incredibly diverse, with wide fluctuations in richness and abundance along the elevation gradient and notable phonological shifts at the community level related to seasonal climate variations (Araújo et al, 2022).…”
Section: Microbial Indicatormentioning
confidence: 99%
“…Utilizing abundant species (or groups of species) with constricted elevation ranges as bioindicators can help to monitor the effects of climate change on the biota and determine how species are adapting through time. According to their findings, imidacloprid residues may be extremely hazardous to non-target insects in the environment, even in areas far from the agro ecosystem where the herbicides were used (Wang et al, 2022). Their findings showed that the Scarabaeinae fauna of Itatiaia is incredibly diverse, with wide fluctuations in richness and abundance along the elevation gradient and notable phonological shifts at the community level related to seasonal climate variations (Araújo et al, 2022).…”
Section: Microbial Indicatormentioning
confidence: 99%
“…In addition, larvae of both species exhibited marked sublethal responses when exposed to lower soil concentrations, including significantly reduced feeding behavior and impaired movement. Another study [61] tested the neonicotinoid imidacloprid at field-relevant concentrations and found that while it caused low mortality in soil-dwelling larvae of the Asian firefly Pyrocoelia analis, its sublethal effects included changes in midgut tissue morphology, convulsive body movements, persistent luminescence and other physiological changes.…”
Section: Collateral Damage: Insecticide Overusementioning
confidence: 99%
“…Among them, imidacloprid is a representative neonicotinoid insecticide. As a competitive inhibitor, it can selectively block nicotinic acetylcholine receptors in insects’ central nervous systems, interrupting normal nervous system signal transmission and killing the insects . However, it also has some drawbacks of easy photooxidation and degradation.…”
Section: Introductionmentioning
confidence: 99%
“…As a competitive inhibitor, it can selectively block nicotinic acetylcholine receptors in insects' central nervous systems, interrupting normal nervous system signal transmission and killing the insects. 26 However, it also has some drawbacks of easy photooxidation and degradation. The overdosage for better insecticidal efficacy would cause adverse ecological and health problems.…”
Section: ■ Introductionmentioning
confidence: 99%